(1328) American food ATD and its impact on the Egyptian economy الطعام الأمريكي وتأثيره على الاقتصاد المصري - moustapha, Mohamed samir (The Institute Of National Planning., 2018)
In the early 1950s U.S. Fawners were calling for stockinette to be done with the huge agree-surpluses threatening their incomes, These surpluses represented a terrible dilemma. The farm lobby would not allow the to be put on the do es tic market. And if dumped on the world market, grain prices would drop by a dollar a bushel. U.S. grain corporations were.